TRAINING OF FUTURE MASTERS FOR PEDAGOGICAL ACTIVITIES IN THE INSTITUTIONS OF HIGHER EDUCATION BY MEANS OF EDUCATIONAL TRAININGS - Melnychuk, Iryna (Mountain School of Ukrainian Carpaty, 2022)
The article deals with the problem of training of future masters of medicine, who did not have received a pedagogical education, for pedagogical activities. It has been generalized that optimal conditions in the described process is using modern pedagogical innovations, which make possible an integration of vocational (in particular, medical) training and pedagogical education, give an opportunity for future masters of medicine testing own professional knowledge, abilities and skills in pedagogical situations that simulate professional-pedagogical, medical-professional activities. Educational trainings may become such technologies. Analysis of scientific literature gave a possibility to generalize that scholars describe theory and practice, contextual and methodical aspects of conducting trainings, reveal the main stages of training technologies, propose methods of organization and conducting training of personal development, which gives an opportunity to identify the essence of trainings in general. The purpose and task of the research is to describe the essence of educational trainings, which appropriate to apply in the vocational training of future masters of medicine for pedagogical activities in the institutions of higher medical education. It has been generalized that in the process of participating the future masters of medicine in educational trainings, participants have ability to identify the main advantages of such work for the use of training forms and methods of teaching in pedagogical activity as a lecturer of medical institution of higher education. It has been stated that the purpose of training of future masters for participating and individual conducting educational trainings in pedagogical activities of lecturers must inform the participants with the main model of preparing for training, which is seen as the basis for making appropriate syllabus that combine the following stages: determining the topic and purpose of training as an image of the future result; determining the composition of the training group; identifying the time resources; formulating the problem; formulating the tasks; selecting appropriate exercises, situational tasks of professional purposes; emphasizing the blocks of the training syllabus and classes for each block; drawing up a scenario of training plan; writing a short training scenario with the purpose of each class and all the necessary materials. Keywords: masters, vocational training, pedagogical activity, educational trainings, training requirements.